IMPLEMENTASI PEMBELAJARAN PJOK PADA PASCA COVID-19 DI SD 130 PEKANBARU KELAS IV A - Saputra, Mhd. Aldo; Vai, Aref; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to find out how successful the implementation of PJOK learning was after the Covid-19 pandemic at SD 130 Pekanbaru class IVA. This type of research uses a research design, quantitative descriptive research with a one shot case study approach (case or opportunity study). The location of this research was carried out at SD 130 Pekanbaru in class IV A. The time of the research began in November 2020 with a sample of 30 students, consisting of 13 boys and 17 girls. The data collection technique is by analyzing the implementation of PJOK learning in the post-Covid-19 pandemic at SD 130 Pekanbaru class IVA. Meanwhile, data analysis in this research uses quantitative descriptive analysis with percentage data used to examine the variables in this research, namely the implementation of PJOK learning in the post-Covid-19 pandemic. Based on the results of research conducted using a questionnaire sheet, it can be seen that, overall, the average student score is 78.88%. This score is in accordance with the calculation results attached on page 56. The average score is in the very good category because the score obtained ranges from 76% - 100%. The average percentage per question indicator gets different results because there are several obstacles, namely: first, some students do not pay attention to the PJOK teacher during the post-covid-19 PJOK learning process. Second, there were some students who did not listen to the researcher when filling out the questionnaire and this resulted in the questionnaire scores obtained being less than optimal.Key Words: Learning Implementation, Post Covid-19